Peroxydisulfate activation by in-situ synthesized Fe3O4 nanoparticles for degradation of atrazine: Performance and mechanism - Keyikoğlu, Ramazan; Karataş, Okan; Khataee, Alireza; Kobya, Mehmet; Can, Orhan Taner; Soltani, Reza Darvishi Cheshmeh (Elsevier, 2020)
Herein activation of persoxydisulfate (PDS) was achieved by in-situ synthesized Fe3O4 nanoparticles (NPs) from a sacrificial iron anode in an electrochemical (EC) cell. The as-synthesized Fe3O4 NPs were characterized to be in spherical and in the nano size. The performance of the process, EC-Fe3O4/PDS, was investigated in terms of atrazine (ATZ) degradation. Optimum process conditions were determined as initial pH of 5, electrolyte (Na2SO4) concentration of 1 mM, a current density of 1.67 A m(-2), PDS concentration of 0.5 mM and initial ATZ concentration of 10 mg L-1. At optimum conditions, the EC-Fe3O4/PDS process could effectively degrade 80% of ATZ in an aqueous solution within a short reaction time of 20 min. The electrical energy consumption of the process was found to be quite low with 0.0307 kWh/m(3). Based on the LC/MS analysis, the degradation pathway of ATZ with seven transformation products was proposed. Finally, a possible mechanism of the EC-Fe3O4/PDS process was put forward, which includes the activation of PDS and the role of radicals in the degradation of ATZ. In conclusion, the combination of Fe3O4 NPs catalyzed PDS oxidation with the EC process was very effective in the degradation of ATZ to dechlorinated final products. The strong synergistic effect makes this process superior to conventional methods due to the high degradation efficiency with low electrical energy and chemical consumption. Application of this method, with very low current density, may not only minimize the electrical energy consumption but also help reduce the sludge production due to the lower iron dissolution.
Keywords: Atrazine; Electrochemical process; Peroxydisulfate activation; Sulfate radical; Magnetite nanoparticles